Obesity and periodontitis in 60–70-year-old men - Gerry Linden (Blackwell Synergy, 2007)
Objective: The aim was to investigate whether there was an association between obesity and periodontitis in a homogeneous group of 60–70-year-old Western European men. The study also explored whether a high body mass index (BMI) in early life predicted poor periodontal status in later life. Methodology: A representative sample of the male population of UK, who were enrolled in a cohort study of cardiovascular disease, was examined between 2001 and 2003. A total of 1362 men with six or more teeth completed a questionnaire, had a clinical periodontal examination and had their weight and height recorded. Multivariable analysis was carried out using logistic regression with adjustment for possible confounders. Models were constructed with low- and high- threshold periodontitis as dependent variables and with BMI as a categorical predictor variable. Low-threshold periodontitis was identified when at least two teeth had X6mm loss of attachment and at least one site had a pocket of X5 mm. High-threshold periodontitis was identified when X15% of sites had X6mm loss of attachment and there was deep pocketing (X6 mm). Modelling was repeated for other predictor variables including BMI at 21 years of age and change in weight since 21 years of age. Results: Two hundred and ninety-eight (21.9%) of the men studied, who had a BMI of >30 kg/m2, were classified as obese. Obesity was associated with low-threshold periodontitis, odds ratio (OR)51.77 (p50.004) after adjustment for confounders. The BMI at 21 years of age did not predict periodontitis in the men investigated. Participants who had experienced a large (>30%) increase in weight during adulthood had an increased risk of poor periodontal condition; however, this was attenuated and no longer significant after adjustment for confounders. Conclusions: It is concluded that obesity was associated with periodontitis in the homogeneous group of 60–70-year-old European men investigated. High BMI levels in early life did not predict periodontitis in later life in the men studied.